2009
DOI: 10.1111/j.1399-3046.2008.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus encephalitis/retinitis in allogeneic haematopoietic stem cell transplant recipient treated successfully with combination of cidofovir and foscarnet

Abstract: We report an 18-yr-old female patient with repeated CMV reactivations after HSCT treated by several pre-emptive courses of virostatic therapy. Seven months after HSCT, she developed CMV encephalitis/retinitis. Initial therapy with GCV and hyperimmune globulin failed, and later on GCV-resistant strain was detected. Continual increase of CMV DNA in peripheral blood led us to combined therapy with CDV and FCV, which was successful and free of severe renal toxicity. To our best knowledge, this is the first reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Fourteen cases of CMV-induced central nervous system (CNS) disease have been reported (Table 1) [ [5][6][7][8][9][10][11][12][13][14][15][16][17]. Of published cases including ours, the median time of onset of CMV CNS disease was 185 days (range 107-285 days).…”
Section: Clonal Expansion Of T Cells In the Skin Is The Hallmark Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen cases of CMV-induced central nervous system (CNS) disease have been reported (Table 1) [ [5][6][7][8][9][10][11][12][13][14][15][16][17]. Of published cases including ours, the median time of onset of CMV CNS disease was 185 days (range 107-285 days).…”
Section: Clonal Expansion Of T Cells In the Skin Is The Hallmark Of Cmentioning
confidence: 99%
“…One survivor was treated with a 8 combination of FCV and CDV after initial therapy with GCV and i.v. Ig [12]. The other survivor received leflunomide, CDV, i.v.…”
Section: Clonal Expansion Of T Cells In the Skin Is The Hallmark Of Cmentioning
confidence: 99%
“…Whatever the hypothesis, our results show that blood samples may not be representative of the resistance status of the virus isolated in the CNS compartment. Interestingly, previous reports of CMV CNS diseases which compared the CMV genotypic resistance profiles in concomitant CSF and blood samples described similar profiles in the two compartments (6,11) or viral compartmentalization, with wild-type CMV in CSF samples and resistant CMV in blood and other sites (5,8,9,13). The authors suggested that decreased CMV fitness due to drug resistance mutations located in UL97 and/or UL54 genes could explain the predominance of wild-type strains in the CSF, even in cases of previous selection of resistant mutants in blood (17).…”
mentioning
confidence: 96%
“…CMV infection of the central nervous system (CNS) is rare in HSCT recipients. Fifteen well-documented cases have been reported (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In most of them, the authors described a high viral load in the CSF contrasting with low peripheral blood viral load (2, 9, 13) or low antigenemia (3,4), suggesting a high level of viral replication in the CNS.…”
mentioning
confidence: 99%
“…This review yielded nine cases of CMV CNS disease in SCT recipients, which meet the criteria for CMV disease of the CNS. [4][5][6][7][8][9][10][11][12] Data from these nine cases along with the two UCLA cases (a total of 11 patients) are summarized in Table 1. Except for one pediatric patient, all patients were adults (median age, 46 years).…”
Section: Review Of Reported Casesmentioning
confidence: 99%